THE DEVELOPMENT OF CHARACTER-BASED DOCUMENTARY FILM FOR THE MATERIALS OF REPRODUCTION SYSTEM - Titin, Titin; Panjaitan, Ruqiah Ganda Putri; Yuliana, Yohanes Gatot Sutapa (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
Technological development that increased rapidly influence the adolescent sexual behavior as well as moral values ​​it has. In order to avoided the deviant behavior and disorders / disruption of reproduction then adolescents needed to understand the importance of maintaining reproductive health. This study aimed to develop a character-based documentary film media that was suitable for used in the learning process on reproduction system materials, so that adolescents can realize the importance of maintaining reproductive health. Character-based documentary film media is expected to shape student character values. The form of this research belonged to research and development. The research consisted of six stages: potential problem, information gathering, product design, design validation, product design improvement, and product trial. The research instrument used in the form of media validation sheet and questionnaire of student responses to character-based documentary film media. The result of validation of media expert on character-based documentary film on reproduction system material was valid. The result showed film-based documentary trials through the test of legibility to students of class XI SMA N 1 Pontianak got percentage of 82.03 with high criteria. The conclusion was that the character-based documentary film on the material of the reproductive system was appropriate to be used as a medium in the learning process.